PERANCANGAN DATABASE ROTI BAKAR SELERA DENGAN MICROSOFT ACCESSDESIGNING A ROTI BAKAR SELERA DATABASE WITH MICROSOFT ACCESS - Alya Zahra Firdaus; Septi Widyastuti; Syarofi Sayiddiya Ulhaq; M. Irzsa Zeqty Gustian; Derry Dardanella (EKSPOLHUM, 2025)
The rapid advancement of information technology, particularly Microsoft Access, presents a significant opportunity for Micro, Small, and Medium Enterprises (MSMEs) to enhance their financial and income data management. Despite these advancements, a notable number of MSMEs, including "Roti Bakar Selera," continue to rely on manual data management processes. "Roti Bakar Selera" is an MSME specializing in a variety of toast products, and like many others, it grapples with the inefficiencies and potential for errors inherent in manual record-keeping. This traditional approach to managing crucial financial information often leads to inaccuracies, hinders operational efficiency, and complicates informed decision-making. This research aims to address these challenges by developing an effective and efficient database management system specifically tailored for "Roti Bakar Selera" using Microsoft Access. The core objective is to design a user-friendly system that streamlines the recording, tracking, and analysis of financial and income data. By implementing this Microsoft Access-based solution, the research anticipates several key benefits. It is expected to significantly reduce data management errors, ensuring greater accuracy in financial reporting. Furthermore, the system will facilitate the seamless recording of financial transactions and income, making the process less cumbersome and time-consuming. Ultimately, the successful application of this system is projected to increase operational efficiency for "Roti Bakar Selera" and support better, data-driven decision-making in the overall management of their business. This study underscores the critical role of accessible technology in empowering MSMEs to achieve greater financial stability and sustainable growth.